Introduction of Traditional Sport Education Games To Students of Public Elementary School 38 Janna -Jannaya in The Era of Technological Development - Syahril, Muhammad; Herlinda Dos Santos, Maria; Aryadi Hardi, Alifiya (Pascasarjana Universitas Mataram, 2025)
The rapid development of digital technology has changed social interaction patterns and physical activity ranging from children to result in decreased participation in traditional sports activities. This service activity discusses the importance of traditional game -based sports education as a strategy to re -introduce cultural heritage and develop students' social skills in the era of technological development. The results of this traditional sports game show that traditional sports have a significant positive impact including, preservation of local culture, character formation based on local wisdom values and the development of motorcycle capabilities and student movement coordination in SD 38 Janna-Jannaya. There are several types of traditional sports games implemented in training activities, namely boy-boyan, jump inch, sodor gobak, and crank. It is hoped that the sports game will one day become a sport that is favored by students in the midst of the rise of the development of digital technology that causes students to access online games and other applications. That is the author raising this title as an effort to re -introduce traditional sports cultural heritage to preserve identity and form a balanced generation in the technology era.